Pelvic Rocking Exercise Menggunakan Birthing ball Mempengaruhi Kemajuan Persalinan Kala I - Siti Husaidah; Desi Ernita Amru; Heroyanto Heroyanto (Midwifery Care Journal, 2023)
Maternal mortality in the Riau Islands Province in 2019 was still dominated by direct causes, namely bleeding and hypertension in pregnancy. In addition, the percentage of other causes which are indirect causes is also quite large, such as prolonged labor around 1.8%. This study aims to determine the effect of Pelvic rocking Exercises using a birth ball on the progress of labor in women in first stage of labor. This study used a pre-experimental study using a static group comparison design with accidental sampling technique. The sample was divided into 2 groups, the intervention group was rocked with a birth ball for active phase mothers for 30 minutes for 2 sessions and the progress of the study in the control group was carried out in November-December 2021 using an independent sample test. The results showed that there was an effect of rocking the pelvis with birthing ball on the progress of labor where the average progress of labor for the status of ball delivery was done and not done, it was different with a p value of 0.00001 0.05. The birth ball status was 138.2 minutes faster than the non-performed birth ball status. The conclusion is that pelvic sway with a birth ball helps the baby rotate to the optimal position and shortens the first stage of labor so as to reduce pain and provide comfort to the mother on the labor process. Suggestion to health workers will be facilitators for mothers in labor and support physiological delivery.